Burgers' Equation and Traffic Flow - Sharma, Amrit; K.C., Durga Jang (Journal of the Institute of Engineering, 2023)
Burgers' equation is a well-known partial differential equation that arises in many areas such as fluid mechanics, non linear acoustics, gas dynamics, and traffic flow. This paper aims to discuss Burgers’ equation and its applications. We begin with the historical development of Burgers’ equation. We mainly focus on the study of traffic flow models where we use the inviscid version of Burger’ equation to model the flow. To this end, we discuss the classification of traffic flow models and some recent development of traffic flow models.